Emergency triage nurses' perceptions of caring behaviors and the safety of the patient during triage encounters: a grounded theory study - Zvonka Fekonja; Sergej Kmetec; Urška Fekonja; Nataša Mlinar Reljić; Majda Pajnkihar; Matej Strnad (BMC, 2024)
Abstract Background Triage is a dynamic process prioritising the patient coming to the emergency department. Caring behaviour and patient safety during the triage process are essential for ensuring a good care experience and treatment outcome. Objective To describe triage nurses' perceptions on caring behaviors and patient safety in the triage area. Design Strauss and Corbin's Grounded theory method was used to develop the model. Methods The study was conducted in the emergency department in northeastern Slovenia. Semi-structured interviews were used for data collection, and 19 triage nurses were selected by theoretical sampling, guided by emerging categories between November 2021 and July 2022. The data analysis was conducted according to Strauss and Corbin's coding framework. Results The analysis of the interviews generated one category: The process of creating a caring and safe triage encounter for the patient, together with two categories that explain the key phenomenon: (1) Triage caring and (2) Safety in the triage process. Within the category "Triage caring", four subcategories were developed: (1) Assurance of triage nurses' presence, (2) Connectedness, (3) Respectful attitude, and (4) Knowledge and skills. The category Safety in the triage process consists of three identified subcategories: (1) Conception and perception of safety, (2) Factors influencing patient safety, and (3) Improving the triage safety. Conclusions The triage nurses' perceptions about caring for the patient and his safety in the triage area show that caring and safety are inseparably linked and coincide when triaging a patient. Namely, caring for the patient means ensuring the patient's safety at the same time. Implications for the nursing field A better understanding of the importance of triage nurses' caring behavior and patient safety emerges from the findings, highlighting the challenges faced in a busy emergency department where nurses must balance providing care and responding to patients' needs while ensuring safety. Findings in the study show that patient care and safety are inseparably linked and coincide when triaging a patient. Moreover, applying caring behaviour during triage encounter results in greater patient safety. No patient or public contribution The study's design, evaluation of the findings, and execution did not need the involvement of patients or the general public. Participants were triage nurses working in the emergency department. Triage nurses were interviewed about their perceptions of triage nurses on caring behaviors and patient safety during triage encounter.